High-Yield Synthesis of Zinc Oxide Nanoparticles from Bicontinuous Microemulsions. (2nd November 2011) - López-Cuenca, S.; Pérez Carrillo, L. A.; Rabelero Velasco, M.; Díaz de León, R.; Saade, H.; López, R. G.; Mendizábal, E.; Puig, J. E.
Abstract : The high-yield synthesis of zinc oxide (ZnO) primary nanoparticles with high purity and with diameters between 6 and 22 nm using bicontinuous microemulsions is reported in this work. The ZnO nanoparticles were made by hydrolysis of Zn(NO3 )2 with NaOH aqueous solution and precipitation, followed by calcination of the precipitate. Higher yields and productivities of ZnO nanoparticles were obtained compared to values produced with w/o micremulsions reported in the literature. Particles were characterized by transmission electronic microscopy (TEM), X-ray diffraction, and atomic absorption spectroscopy.